2021
DOI: 10.24843/jsgs.2021.v05.i02.p03
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Creative Arts Therapy on Stress Level and Blood Pressure of The Elderly With Hypertension

Abstract: The elderly are vulnerable to hypertension due to the accumulation of unhealthy lifestyles for a long time and can be exacerbated by the stress due to the inability to adapt to the decline in physical conditions, changes in roles and social relations, economic ability, degenerative diseases and treatment in the long term. Risk factors for hypertension can caused by stress. Stress management can be done with a combination of creative arts therapy that is singing, drawing, and storytelling which has a relaxing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Art therapy and artmaking may reduce cortisol levels ( Visnola et al, 2010 ; Kaimal et al, 2016 ; Beerse et al, 2019 , 2020 ) that may improve other psychosocial outcomes of mood, self-efficacy, and perceived stress ( Kaimal and Ray, 2017 ; Beerse et al, 2019 ). Other preliminary studies have explored blood pressure as a biomarker to examine artmaking as an effective stress reducer ( Schrade et al, 2011 ; Utami et al, 2021 ). Futterman Collier et al (2016) found that textile arts have a mood enhancing effect when measured using salivary levels of IL-beta, a proinflammatory cytokine.…”
Section: Active Factors In Art Therapy Relevant For Ptsdmentioning
confidence: 99%
“…Art therapy and artmaking may reduce cortisol levels ( Visnola et al, 2010 ; Kaimal et al, 2016 ; Beerse et al, 2019 , 2020 ) that may improve other psychosocial outcomes of mood, self-efficacy, and perceived stress ( Kaimal and Ray, 2017 ; Beerse et al, 2019 ). Other preliminary studies have explored blood pressure as a biomarker to examine artmaking as an effective stress reducer ( Schrade et al, 2011 ; Utami et al, 2021 ). Futterman Collier et al (2016) found that textile arts have a mood enhancing effect when measured using salivary levels of IL-beta, a proinflammatory cytokine.…”
Section: Active Factors In Art Therapy Relevant For Ptsdmentioning
confidence: 99%